Single‐Cell Transcriptomics of Engineered Cardiac Tissues From Patient‐Specific Induced Pluripotent Stem Cell–Derived Cardiomyocytes Reveals Abnormal Developmental Trajectory and Intrinsic Contractile Defects in Hypoplastic Right Heart Syndrome - Lam, Yin‐Yu; Keung, Wendy; Chan, Chun‐Ho; Geng, Lin; Wong, Nicodemus; Brenière‐Letuffe, David; Li, Ronald A.; Cheung, Yiu‐Fai (Journal of the American Heart Association, 2020)
Background To understand the intrinsic cardiac developmental and functional abnormalities in pulmonary atresia with intact ventricular septum (PAIVS) free from effects secondary to anatomic defects, we performed and compared single-cell transcriptomic and phenotypic analyses of patient- and healthy subject-derived human-induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) and engineered tissue models. Methods and Results We derived hiPSC lines from 3 patients with PAIVS and 3 healthy subjects and differentiated them into hiPSC-CMs, which were then bioengineered into the human cardiac anisotropic sheet and human cardiac tissue strip custom-designed for electrophysiological and contractile assessments, respectively. Single-cell RNA sequencing (scRNA-seq) of hiPSC-CMs, human cardiac anisotropic sheet, and human cardiac tissue strip was performed to examine the transcriptomic basis for any phenotypic abnormalities using pseudotime and differential expression analyses. Through pseudotime analysis, we demonstrated that bioengineered tissue constructs provide pro-maturational cues to hiPSC-CMs, although the maturation and development were attenuated in PAIVS hiPSC-CMs. Furthermore, reduced contractility and prolonged contractile kinetics were observed with PAIVS human cardiac tissue strips. Consistently, single-cell RNA sequencing of PAIVS human cardiac tissue strips and hiPSC-CMs exhibited diminished expression of cardiac contractile apparatus genes. By contrast, electrophysiological aberrancies were absent in PAIVS human cardiac anisotropic sheets. Conclusions Our findings were the first to reveal intrinsic abnormalities of cardiomyocyte development and function in PAIVS free from secondary effects. We conclude that hiPSC-derived engineered tissues offer a unique method for studying primary cardiac abnormalities and uncovering pathogenic mechanisms that underlie sporadic congenital heart diseases.